2014
DOI: 10.1002/jwmg.797
|View full text |Cite
|
Sign up to set email alerts
|

Demography, reproductive ecology, and variation in survival of greater sage-grouse in northeastern California

Abstract: We examined demographic parameters and factors influencing nest survival of female greater sage‐grouse (Centrocercus urophasianus) in northeastern California. Additionally, we used known‐fate models in program MARK to examine bi‐weekly survival rates of females over an 8‐month period (Mar–Oct, 2007–2009). Nest survival rate, assuming a 38‐day exposure period, was 41% and was positively associated with grass height (trueβˆ = 0.03, SE = 0.02), but the 95% confidence interval overlapped 0 (95% CI = −0.007–0.767) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
(111 reference statements)
0
18
1
Order By: Relevance
“…These results are driven, in part, by the relatively low reproductive success of female sage‐grouse. Although individual heterogeneity has been demonstrated for female sage‐grouse (Blomberg et al b , Caudill et al a , Davis et al ), reproductive success for sage‐grouse is also low in general (Connelly et al ) and in particular for this system. When coupled with lower survival due to reproductive costs (Blomberg et al b ), only a small proportion of hens with broods that are removed through additive harvest are expected to reproduce successfully again the following year, had they not been harvested.…”
Section: Applied Examples For Greater Sage‐grousementioning
confidence: 99%
See 2 more Smart Citations
“…These results are driven, in part, by the relatively low reproductive success of female sage‐grouse. Although individual heterogeneity has been demonstrated for female sage‐grouse (Blomberg et al b , Caudill et al a , Davis et al ), reproductive success for sage‐grouse is also low in general (Connelly et al ) and in particular for this system. When coupled with lower survival due to reproductive costs (Blomberg et al b ), only a small proportion of hens with broods that are removed through additive harvest are expected to reproduce successfully again the following year, had they not been harvested.…”
Section: Applied Examples For Greater Sage‐grousementioning
confidence: 99%
“…However, compensation of harvest losses through increased post-harvest survival can occur at any point between the timing of harvest mortality and the birth of young the following spring; compensation need not be restricted to the winter. Recent work has demonstrated that sagegrouse survival may be reduced during the fall for both juveniles (Blomberg et al 2014, Caudill et al 2014b) and adult females (Blomberg et al 2013b, Davis et al 2014). This period of high non-harvest mortality occurs between August-October (Blomberg et al 2013a(Blomberg et al , b, 2014Caudill et al 2014b;Davis et al 2014), and sage-grouse hunting seasons typically begin in September and may continue into October (Table 1).…”
Section: Applied Examples For Greater Sage-grousementioning
confidence: 99%
See 1 more Smart Citation
“…Clutch size is generally high (species mean  7.4  0.8 SE; Schroeder et al 1999), but is variable among individuals and breeding attempts (may range from 3 to 12 eggs within a single population; Blomberg et al 2014a). Sage-grouse have intermediate annual survival probabilities (species mean for adult females  0.58; Taylor et al 2012), and female sage-grouse experience reproductive costs in the form of reduced survival following successful reproduction (Blomberg et al 2013a, Davis et al 2014, Dinkins et al 2014. Population growth in sage grouse is sensitive to both adult survival and some components of reproduction (e.g.…”
mentioning
confidence: 99%
“…Over the past 50 years, ecologists have used radiotelemetry to study survival, movement, and behavior of waterbirds, including shorebirds, cranes, grebes, loons, ducks, geese, swans, albatrosses, penguins, and alcids (e.g., Greenwood and Sargeant 1973, Klugman and Fuller 1990, Meyers et al 1998, Green et al 2004, Mulcahy et al 2011. In particular, telemetry-based breeding-season survival rates and habitat selection patterns have informed management and conservation practices of game birds (Cowardin et al 1985, Davis et al 2014, Howerter et al 2014, Gibson et al 2016. Usually, investigators make the fundamental assumption that capture and marking techniques do not bias parameters of interest such as behavior, reproductive effort, survival, or movement (Barron et al 2010).…”
mentioning
confidence: 99%